2018
DOI: 10.1136/openhrt-2018-000877
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of β-blocker adherence in cardiac inherited disease

Abstract: ObjectiveThe cardiac inherited disease (CID) population has suboptimal adherence to long-term β-blocker therapy, which is known to be a risk for sudden cardiac death. This study aimed to identify the clinical and psychosocial variables associated with non-adherence in this population.Methods130 individuals (aged 16–81 years, median: 54) from the New Zealand Cardiac Inherited Disease Registry taking β-blockers participated: 65 (50%) long QT syndrome, 42 (32%) hypertrophic cardiomyopathy and 23 (18%) other. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Medications are recommended for many patients with inherited cardiovascular diseases, especially for those with arrhythmia syndromes. For young patients, adherence to β-blocker medication can be strongly influenced by psychological and social factors (Ingles et al 2015;O'Donovan et al 2018). In the setting of LQTS, β-blocker therapy is shown to reduce the likelihood of cardiac arrhythmias and is an important first-tier treatment (Chockalingam et al 2012).…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medications are recommended for many patients with inherited cardiovascular diseases, especially for those with arrhythmia syndromes. For young patients, adherence to β-blocker medication can be strongly influenced by psychological and social factors (Ingles et al 2015;O'Donovan et al 2018). In the setting of LQTS, β-blocker therapy is shown to reduce the likelihood of cardiac arrhythmias and is an important first-tier treatment (Chockalingam et al 2012).…”
Section: Research Findingsmentioning
confidence: 99%
“…In the medical literature, studies of adherence to any prescribed therapy indicate that psychological factors, including illness perception, beliefs about the medication, self-efficacy (i.e., their confidence in their ability to take the medication), and psychosocial well-being, are important determinants of medication adherence (Jin et al 2008). One study examining adherence to β-blocker therapy among patients with LQTS found 16% were not adherent (O'Donovan et al 2018). Those who were younger and had an inherited arrhythmia syndrome reported lower self-efficacy, greater concerns, low necessity beliefs, and poorer understanding of their disease.…”
Section: Research Findingsmentioning
confidence: 99%
“…Alternatively, this might be due to fluctuations in the drug serum levels and its corresponding antiarrhythmic effect on the EST. Non-adherence—a well-known problem in the treatment of inherited cardiac arrhythmias 23 —prior to the EST might underlie these fluctuations. This is in line with our observation that the difference in maximum heart rate between ESTs was associated with the odds for an increased ΔVAS and the repeatability of the maximum heart rate in the EST-pairs with a ΔVAS > 1 was substantial but almost perfect in the pairs with a ΔVAS of 0 and 1.…”
Section: Discussionmentioning
confidence: 99%
“…In a study from New Zealand, adequate adherence was reported in only 50% of LQT patients 44. Side effects are frequent and contribute, with illness perception and believe in medication, to non-adherence 44 45. Obviously, this has potentially serious impact on the freedom from arrhythmic events.…”
Section: Introductionmentioning
confidence: 99%